Strengthening Village Economies as a Buffer Zone for Achieving the SDGs: The Role of Human Resource Management in the Halal Industry - Agus Supriyanto; Agung Slamet Sukardi; Widi Savitri Andriasari; Dennyca Hendriyanto Nugroho (Bulletin of Community Engagement, 2026)
This study aims to explore the role of human resource management in strengthening village economies to support the achievement of halal certification for Micro, Small, and Medium Enterprises (MSMEs), as well as to identify the challenges encountered throughout the certification process. Using a quantitative approach complemented by the Analytical Hierarchy Process (AHP) method, this research identifies various factors influencing the success of halal certification, including income level, access to resources, and support from local government. Data were collected through questionnaires and in-depth interviews with 100 respondents representing MSMEs that have obtained, are currently undergoing, or are planning to apply for halal certification. The study also examines the contribution of halal certification to the achievement of the Sustainable Development Goals (SDGs), particularly in poverty alleviation, inclusive economic growth, and sustainable consumption and production. The findings indicate that village economies with their growing MSME sector hold significant potential to support the achievement of halal certification. Halal certification is shown to have a positive impact on MSME competitiveness, expanding market access, and supporting the economic sustainability of rural communities. This research recommends the enhancement of training programs, policy support, and cross-sector collaboration to accelerate the halal certification process and strengthen MSME capacity in supporting the achievement of the SDGs.